Research on Risk Control under the Background of Electricity Futures Market - Chang Suyuan; Liu Dunnan; Li Xiaoyu (E3S Web of Conferences, 2020)
In the process of electricity marketization, the electricity futures market is an effective means to avoid the risk of electricity price fluctuations. Based on the background of the electricity futures market, this article first analyzes the physical and market factors of the price fluctuation risk in the electricity market; then, it studies the principle and implementation effects of the power futures hedging function; finally, the manufacturer’s strategy of hedging based on the price difference between the spot price of electricity and the price of forward contracts has been studied in detail. This article believes that the electricity futures market can effectively hedge the spot market risk, and hedging strategies based on the difference between the spot price and the forward price are better.